Bibliometric Analysis on Defence Forces Management Research Using Scopus for the Period of 2010-2024 - Gupta, Anand; Bajpai, Sudhanshu (Journal of Data Science, Informetrics, and Citation Studies)
This study presents a comprehensive bibliometric analysis of research on defence force management, examining the funding sources, document types, leading journals, authorship networks, and subject areas contributing to this field. The data for this bibliometric analysis was retrieved from the Scopus database for the period of 2010-2024. 1495 records were retrieved and analysed in this study. The U.S. Department of Defence emerges as the top sponsor, with 16 publications focused on enhancing military management, followed by the National Institutes of Health with 13 publications, reflecting the growing intersection between military operations and health. The analysis reveals a diverse funding landscape, involving international and health-related organizations, highlighting the interdisciplinary nature of this field. Publications are predominantly articles (54.7%), followed by conference papers (27.6%), with key contributors such as Greenberg, N. and Cohen, S.P. playing significant roles in shaping the research landscape. The study also tracks publication trends, showing a significant rise in research output between 2016 and 2020, followed by a decline from 2021 onwards. The subject areas include Medicine, Engineering, Social Sciences, and Computer Science, emphasizing the holistic approach required for managing modern defence forces. Research in medical and psychological management, energy efficiency, and disaster response has been particularly prominent in recent years, reflecting the on-going evolution of defence force management research.
Keywords: Bibliometrics; Scientometrics; Strategic Management; Scopus; Military; Defence Forces.